The Effectiveness of History Learning Using a Learning Model E-Learning - Wibowo, Heros Satrio (Universitas Negeri Semarang, 2018)
The results of preliminary observations about the learning process at SMA 9 Semarang reveal that the school must utilize model-based learning or e-learning facilities to procure models. Despite having adequate e-learning resources such as hotspot areas, LAN, projectors, and computers, these tools must be employed more effectively in the learning process. The many advantages of the e-learning model, including enhanced engagement and accessibility of materials, have led the authors to be interested in experimenting with implementing e-learning in teaching methods at the school. This study aims to address several fundamental problems: (1) how the application of learning models on the lecture material of Colonialism and Imperialism in Indonesian West is implemented in Class XI Social at High School 9 Semarang, (2) how the implementation of e-learning materials on Colonialism and Imperialism in Indonesian West is carried out in Class XI social education at High School 9 Semarang, and (3) how effective is the use of e-learning materials on Colonialism and Western Imperialism in Indonesia in enhancing the learning of history in Class XI Social at High School 9 Semarang. These questions will guide the research to explore the potential benefits and challenges of integrating e-learning into the traditional teaching methods at the school. Through this study, the authors hope to provide insights into the effectiveness of e-learning in improving the educational experience and outcomes for students and identify best practices for its implementation in similar educational settings.